The Supreme Audit Office of the Czech Republic - Skotnicki, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article presents the genesis, evolution, current political position and the subjective and objective scope of the Supreme Audit Office of the Czech Republic. Its origins date back to the times of Czechoslovakia after the First World War. In later years, he was replaced by the Ministry of Control. The laxity of the current constitutional regulation of this body does not allow to precise determination of its political position, and although it cannot be considered as the fourth estate it is undoubtedly specific. The subjective and subjective scope of the control exercised by this body also raises doubts.